2014
DOI: 10.1017/s0007114514000440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tryptophan supplementation on diet-induced non-alcoholic fatty liver disease in mice

Abstract: Intestinal serotonin (5-hydroxytrypamine, 5-HT) metabolism is thought to play a role in gut functions by regulating motility, permeability and other functions of the intestine. In the present study, we investigated the effect of tryptophan (TRP), the precursor of 5-HT, supplementation on intestinal barrier functions and non-alcoholic fatty liver disease (NAFLD). An established mouse model of NAFLD induced by feeding a fructose-rich diet (N group) was used in the present study. TRP was administered orally for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 33 publications
6
55
0
5
Order By: Relevance
“…45 In our study, NAFLD-induced mice showed an identical trend to those used in previous studies in that a significant increase is seen in the liver weight of NAFLDinduced mice. 2,5 In addition, we suggest that consumption of soybean embryos inhibits hepatic TG accumulation, and high-dose soybean embryos were more effective than lowdose consumption of soybean embryos. We reached this conclusion based on the significantly lower liver weights of mice fed soybean embryos.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…45 In our study, NAFLD-induced mice showed an identical trend to those used in previous studies in that a significant increase is seen in the liver weight of NAFLDinduced mice. 2,5 In addition, we suggest that consumption of soybean embryos inhibits hepatic TG accumulation, and high-dose soybean embryos were more effective than lowdose consumption of soybean embryos. We reached this conclusion based on the significantly lower liver weights of mice fed soybean embryos.…”
Section: Discussionmentioning
confidence: 83%
“…5 The results of this study are in agreement with previous findings of studies on mice fed high-fat diets. 2,44 The NAFLD is characterized by hepatic TG accumulation. It is caused by metabolic imbalance, which results from an increase in hepatic TGs and FFAs and a decrease in the release of TGs and FFAs from the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing tryptophan availability for the microbiota would be the most straightforward strategy to promote indole production in vivo . Interestingly, tryptophan supplementation in mice was shown to modulate the progression of NAFLD, although conflicting results were obtained and the potential link with the production of indole was not explored (53, 54). In a preliminary experiment, we found that free dietary tryptophan supplementation (0.5% w/v in drinking water) in mice failed to increase indole production, as evaluated by excretion of I3S in the urine, a commonly used proxy for intestinal production of indole (55, 56).…”
Section: Discussionmentioning
confidence: 99%